Morphological profile of the best pan-american team handball players by game position - Maria Fátima Glaner (Universidade Federal de Santa Catarina, 1999)
The purpose of this study was to characterize the morphological variables, by game position (GP), of male athletes who participated on the X Pan-American Games in Team Handball (XPGTH) and also to analyze the very same variables of the best athletes in relation to other athletes who played in the same GP. 103 athletes were measured, and the national team coaches who participated in the XPGTH selected the best seven players in the Pan-American Games, for each game position. The morphological variables characterized were: body mass; stature (ST); arm span (AS); lower extremity length (LEL); hand and wrist breadth; forearm perimeter and body composition. The results obtained demonstrated that many athletes had morphological characteristics beyond the ideal for this sport. The Z scores indicate that the best athletes from different GP (goalkeeper, backcourt, wings and circle runner) exhibited larger morphological characteristics in relation to the means for the other players in their respective GP. The best goalkeeper and the circle runner were the only ones whose scores were higher in relation to each GP, respectively, when the entire group of morphological variables were considered together. The variables that demonstrated greater morphological development for the best athletesin the 4 GP, compared to the other athletes, were: ST, AS, LEL, % fat and lean body mass. ARESUMO Objetivou-se caracterizar as variáveis morfológicas dos atletas, por posição de jogo (PJ), das seleções participantes dos X Jogos Pan-Americanos de Handebol Masculino (XJPHM), e analisar as variáveis dos melhores atletas de cada PJ em relação aos demais das respectivas PJ. Mensurou-se 103 atletas. Sete deles foram selecionados por PJ, pelos treinadores das seleções participantes dos XJPHM, como os melhores da competição. Caracterizou-se as variáveis morfológicas: massa corporal; estatura (ES); envergadura (ENV); comprimento dos membros inferiores (CMI); diâmetros palmar e rádio-ulnar; perímetro do antebraço e composição corporal. Os resultados obtidos evidenciam que vários atletas apresentam características morfológicas aquém do ideal para a modalidade. Os escores Z indicam que os melhores atletas das diferentes PJ (goleiro, armadores, extremas e pivô) apresentam características morfológicas demasiadamente avantajadas em relação aos valores médios dos demais atletas das respectivas PJ. Os melhores pivô e o goleiro são os atletas que apresentam escores mais elevados em relação aos demais atletas das respectivas PJ, do que os melhores armadores e extremas, quando considerado todo o conjunto das variáveis morfológicas. As variáveis que mais evidenciam o avantajamento morfológico dos melhores atletas das 4 PJ, em relação aos demais atletas são: ES, ENV, CMI, % de gordura e massa corporal magra.